Расчетно-экспериментальное исследование термодинамической эффективности тепловых насосов - Тарасова, В.А. (Проблемы машиностроения, 2016)
Предложена новая методика тестирования термодинамической эффективности теплового насоса, которая позволяет по ограниченному числу замеряемых параметров оценить энергоемкость выработанного тепла. С использованием энтропийно-статистического подхода Гордона–Нджу сформирована полуэмпирическая термодинамическая модель, позволяющая учесть реальную величину внутренней диссипации энергии в цикле и оценить эффективность теплового насоса при работе с частичной нагрузкой. Создан программный комплекс по обработке результатов мониторинга теплонасосной системы тепло- и холодоснабжения административного здания в режиме реального времени. По результатам тестирования работы теплового насоса VMN430L выявлено, что он эксплуатируется в режиме неполной загрузки (80%). Это приводит к увеличению потерь от необратимости в цикле на 7,3÷10% по сравнению с режимом полной загрузки. Запропоновано нову методику тестування термодинамічної ефективності теплового насоса, яка дозволяє за обмеженим числом параметрів, що заміряються, оцінити енергоємність виробленого тепла. З використанням ентропійно-статистичного підходу Гордон-Нджу сформовано напівемпіричну термодинамічну модель, яка дозволяє врахувати реальну величину внутрішньої дисипації енергії в циклі і оцінити ефективність теплового насоса при роботі у режимі з частковим навантаженням. Створено програмний комплекс для обробки результатів моніторингу теплонасосної системи тепло- і холодопостачання адміністративної будівлі в режимі реального часу. За результатами тестування роботи теплового насоса VMN430L виявлено, що він експлуатується в режимі з неповним навантаженням (80%). Це призводить до збільшення втрат від незворотності в циклі на 7,3÷10% в порівнянні з режимом повного завантаження. Proposed the methodology of monitoring of heat pump allows real-time to exercise thermodynamic testing of the heat pump for a limited amount of measured parameters, including operation at partial load. The essence of the technique is that on the basis of data thermodynamic efficiency statistics catalogs of manufacturers of chillers and heat pumps the regression equation is formed for determine the loss of irreversibility in the cycle. This relationship serves as the reference characteristics of heat pump for his diagnosis in real time, with only available data on the coolant temperature at the inlet of the evaporator and condenser, as well as indications of heat and electricity. Monitoring of the heat pump VMN430L in the heating system of the office building showed that this model is mainly operated in partial load operation. This led to a substantial increase in the amount of internal energy dissipation in the cycle and as a result increased power consumption. While reducing the cooling capacity by 50% with respect to full load the irreversibility losses varied by only in 1%. In addition, while raising the temperature of ambient air and below 0 °C and increasing its humidity to 85% significantly reduces the effectiveness of heat pump. Thus, our monitoring showed the ineffectiveness of this model. By the way, it should be noted that revealed by the settlement and pilot testing shortcomings are not typical for the current generation of chillers and heat pumps (for example, chillers Clivet, Trane).